A price-performance analysis of the protective capabilities of wholesale bicycle helmets. (18th August 2021) - Bland, Megan L.; Rowson, Steven
Abstract: Objective: Although bicycle helmets are an effective countermeasure against head injury, many cyclists do not wear one. One avenue for facilitating widespread helmet use is through community-driven helmet safety initiatives, which often give away or subsidize wholesale helmet models that are manufactured at a low price point. However, the impact performance of such helmets during real-world accident conditions has yet to be explored. The present study seeks to investigate trends between wholesale bicycle helmet price and protective capabilities. Methods: Nine common wholesale helmet models (price range 3.65–12.95) were evaluated according to the bicycle Summation of Tests for the Analysis of Risk (STAR) methodology, which analyzes helmet performance in 24 oblique impact tests reflecting common cyclist head impact conditions. Resulting head peak linear acceleration (PLA) and peak rotational velocity (PRV) were collected and used to predict risk of concussion. Concussion risks were then combined using the STAR algorithm in order to summarize each model's risks into a single, weighted metric. Results: Large ranges in kinematic results led to large variations in concussion risks between helmets, and in turn, large variations in STAR values (13.5–26.2). Wholesale helmet price was not significantly associated with STAR, although incorporating 30 previous bicycle helmet STAR results produced a weak negative correlation between price and STAR overall. Nonetheless, the best-performing wholesale helmet produced one of the lowest overall STAR values for a price of 6.45. Helmet style was instead a superior predictor of STAR, with multi-sport style helmets producing significantly higher linear accelerations and resulting STAR values than bike style helmets. Conclusions: These results show that the impact performance of wholesale helmets ranges considerably despite their low price-points. Results can also guide helmet safety promotion organizers toward distributing wholesale bicycle helmet models associated with lower overall concussion risks.